A versatile metal–organic nanoplatform in combination with CXCR4 antagonist and PD-L1 inhibitor for multimodal synergistic cancer therapy and MRI-guided tumor imaging. (December 2022) - Liu, Di; He, Hongliang; Kong, Fei; Cao, Yixiang; Zang, Fengchao; Ma, Ming; Gu, Ning; Zhang, Yu
Abstract: Currently, multimodal synergistic nanoplatform emerges as an important cancer therapy paradigm, however, multimodal synergistic theranostic nanoplatform remains to be developed. Herein, using the mouse model of breast cancer, a versatile multimodal synergistic theranostic nanoplatform is rationally designed and synthesized for enhancing chemodynamic therapy (CDT), overcoming immunosuppression within tumor microenvironment, and inhibiting metastasis as well as tracking tumor. To fulfill our design, a composite Fe/Mn magnetic nanoparticle is first synthesized by loading with Fe3 O4 and BMS-202 (PD-L1 inhibitor) within a poly(lactide-co-glycolide)-based nanoparticle core, which are further modified with in situ synthesis of MnO2 layer. Then, the composite metal-organic nanoparticle is coated with two targeting moieties hyaluronic acid (HA) and AMD3100 (CXCR4 antagonist), respectively, to achieve the multimodal synergistic theranostic nanoplatform (FMN-BMS@HA+AMD). With surface targeting modification, FMN-BMS@HA+AMD exhibits enhanced tumor accumulation, where it effectively consumes endogenous glutathione to generate Mn 2+ allowing for the enhanced CDT effect, alleviates tumor hypoxia by O2 generation and reverses the tumor immunosuppression. FMN-BMS@HA+AMD blocks CXCR4 receptor on cancer cells, thus suppressing the CXCR4-mediated cancer metastasis and invasion. Additionally, FMN-BMS@HA+AMD would synchronously be achieving tumor tracking by T1 -T2 dual-mode magnetic resonance imaging. Collectively, this strategy holds a novel multimodal synergistic theranostics for effective cancer management. Graphical Abstract: Herein, using the mouse model of breast cancer, we developed a versatile multimodal synergistic theranostic nanoplatform for enhancing chemodynamic therapy (CDT), overcoming tumor microenvironment immunosuppression, hypoxia, and metastasis as well as tracking tumor. ga1 Highlights: The multimodal synergistic therapy exerts remarkable synergistic effects ("1 + 1 >2″). The multimodal synergistic inhibits tumor growth and metastasis, and boosts immune effects. Encapsulated Fe3 O4 and generated Mn 2+ would synchronously enhance magnetic resonance imaging-mediated tumor tracking.